1979
DOI: 10.1080/00103627909366919
|View full text |Cite
|
Sign up to set email alerts
|

Changes in herbage chemical composition due to proportion of species in alfalfa‐orchardgrass mixtures

Abstract: Legumes and grasses are widely grown in mixtures throughout the United States and Canada. This study was conducted to determine the changes in chemical composition of herbage that occur as proportion of legume and grass change in the mixture. Composition of mixtures of alfalfa (Medicago sativa L.) and orchardgrass (Dactylis glomerata L.) were studied after their herbage had been mixed by weight into seven different proportions: 100% alfalfa -0% orchardgrass, 80% -20%, 65% -35%, 50% -50%, 35% -65%, 20% -80%, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…Kura clover seasonal forage DM proportions in mixtures reported by Zemenchik et al (2001) were negatively correlated with NDF concentrations over all years at Arlington ( r = 0.78) and at Lancaster ( r = 0.78). This is consistent with observations made by Napitupulu and Smith (1979) for alfalfa–OG mixtures. Similarly, the proportion of birdsfoot trefoil in mixtures was negatively correlated to NDF concentrations over all years at Arlington ( r = 0.85) and Lancaster ( r = 0.71).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Kura clover seasonal forage DM proportions in mixtures reported by Zemenchik et al (2001) were negatively correlated with NDF concentrations over all years at Arlington ( r = 0.78) and at Lancaster ( r = 0.78). This is consistent with observations made by Napitupulu and Smith (1979) for alfalfa–OG mixtures. Similarly, the proportion of birdsfoot trefoil in mixtures was negatively correlated to NDF concentrations over all years at Arlington ( r = 0.85) and Lancaster ( r = 0.71).…”
Section: Resultssupporting
confidence: 93%
“…Similarly, birdsfoot trefoil proportions in all mixtures were positively correlated to CP concentrations over all years at Arlington ( r = 0.89) and Lancaster ( r = 0.86). These correlations are consistent with the work of Napitupulu and Smith (1979) for alfalfa and OG mixtures and Barnett and Posler (1983) for red clover in mixture with several perennial grasses, including KBG and SBG.…”
Section: Resultssupporting
confidence: 89%
“…The net effect is a greater flux of digestible nutrients to the target tissues, and increased productiv ity. The higher the percentage legume composition of a legume-grass mixture, the greater will be the difference in quality between the legume-based and N fertilizer-based forages (Napitupulu and Smith, 1979).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Increasing the N input level in a system based solely on symbi otic N fixation results from increasing the legume yield and the N fixa tion capacity of the legume component, which in turn are closely related to the legume proportion in the sward (Hoglund and Brock, 1978;Vallis, 1978). Since legumes generally exhibit higher digestibilities and in take potentials than grasses at similar stages of maturity (Thornton and Minson, 1973), increasing the legume proportion could favorably alter the quality of the herbage (Napitupulu and Smith, 1979). In tissue analyses of alfalfa-orchardgrass mixtures, Napitupulu and Smith (1979) found that the percentage cell wall constituents (an indicator of intake potential) increased from 39 to 59% as the percentage alfalfa decreased from 100 to 0%.…”
Section: Fate Of Excreted Jjx Pasturesmentioning
confidence: 99%
See 1 more Smart Citation